How accurate was Bronze Age weighing in Western Europe?. (December 2021) - Poigt, Thibaud; Comte, Florent; Adam, Louis
Highlights: Reflexion about the use of weights and balances during the Late Bronze Age in Western Europe. 3D simulations to observe mechanical behaviour and constraints of Bronze Age balance beams. We develop new protocols to study the accuracy of Late Bronze Age weighing instruments using digital tools. Abstract: This paper aims to bring new insights about weighing practices and instruments during Late Bronze Age in Western Europe. Northern France and Southern England share the particularity of providing tiny balance beams and weights dedicated to weigh small quantities. It is traditionally accepted that most of the Bronze Age weights found in Western Europe correspond roughly to a same practice built around one metrological system. Nevertheless, the deviations observed between several weights which should correspond to the same values in the metrological system raise questions about the accuracy of the Bronze Age balances. This paper synthetizes the general categories of weights and beams used during the Bronze Age in Northern France and Southern England and their main characteristics. Using new mathematical and digital protocols – sensitivity analysis, 3D modelling and simulation, and finite element analysis – we highlight the main mechanical features of the Bronze Age balances, the accuracy that should be expected with them and their resistance to use. Our results show than ancient balances were way more accurate that what is generally estimated. They show that most of them should probably allow to see differences between the loading of the two pans less than 0.5 g in most of cases. These results also raise new interpretations about the use of metrological systems during the Bronze Age considering that certain weights, generally interpreted as the same value, would appear as completely different if they were put on each pan of such a balance. The resistance simulations also show that the bone beams were very robust and could support loading much heavier than the weights identified for the same period.